The ESAF at Ten Years : Economic Adjustment and Reform in Low-Income Countries. (Occasional Papers; Occasional Paper, 1998)
For over 10 years, the IMF has supported adjustment and reform programs in many of its low-income members through two facilities established specifically for that purpose - the Enhanced Structural Adjustment Facility (ESAF) and its precursor the Structural Adjustment Facility (SAF). By the end of 1994, 36 countries had availed themselves of these facilities, in support of 68 multi-year programs. This study summarizes the findings of a review of the experience under these programs and of economic developments in the countries that undertook them.